'A whole society, with its own economic system': the reciprocal and capitalist configurations of American DIY music scenes. Issue 1 (2nd January 2023) - Verbuč, David
ABSTRACT: In this article, I examine the alternative economics of reciprocity in American DIY (do-it-yourself) culture. Through long term ethnographic study of local and translocal DIY scenes, including shows, spaces, and touring practices, I reveal a plethora of reciprocal musical and extra-musical activities that enable the creation of alternative DIY worlds. Yet I also highlight how these alternative economic systems of reciprocity coexist with capitalist ones. Drawing on Arjun Appadurai's theories of value and commodity (1986), alongside other authors who examine the co-existence of different economic systems, I chart how DIY practitioners tactically navigate the boundaries between these reciprocal and capitalist economic systems and worlds. These socio-economic relations, I argue, also shape DIY sounds and aesthetics, as well as contribute to distinct musical values, discourses and practices.